2003
DOI: 10.1074/jbc.m211779200
|View full text |Cite
|
Sign up to set email alerts
|

The Autoxidation of Tetrahydrobiopterin Revisited

Abstract: It has been known for quite some time that tetrahydrobiopterin (H4B) is prone to autoxidation in the presence of molecular oxygen. Evidence has been presented that in this process superoxide radicals may be released, although their intermediacy never has been directly proven. In the present study, the autoxidation of H4B was reinvestigated with the aim to find direct evidence for superoxide formation. By means of two specific assays, namely elicitation of luminescence from lucigenin and ESR-spectrometric detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 69 publications
0
47
0
Order By: Relevance
“…Given that the present study was performed to simulate the clinical setting, the use of a chronically instrumented conscious animal model was believed to be essential, because open-chest preparations are associated with a number of potentially confounding factors that may interfere with myocardial infarction 14 and/or ischemic PC. 15 Moreover, because BH 4 is auto-oxidized in a radical reaction 16 and is oxidized by NO 17 and peroxynitrite, 18,19 it seemed important to avoid experimental conditions, such as surgical trauma, that may lead to exaggerated generation of free radicals. 20 Accordingly, all of the studies reported herein were performed in closed-chest, awake animals in an effort to test the effect of hypercholesterolemia on late PC under conditions that were Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the present study was performed to simulate the clinical setting, the use of a chronically instrumented conscious animal model was believed to be essential, because open-chest preparations are associated with a number of potentially confounding factors that may interfere with myocardial infarction 14 and/or ischemic PC. 15 Moreover, because BH 4 is auto-oxidized in a radical reaction 16 and is oxidized by NO 17 and peroxynitrite, 18,19 it seemed important to avoid experimental conditions, such as surgical trauma, that may lead to exaggerated generation of free radicals. 20 Accordingly, all of the studies reported herein were performed in closed-chest, awake animals in an effort to test the effect of hypercholesterolemia on late PC under conditions that were Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide is formed in vivo by NADPH oxidase in phagocytic cells MS 20120387 Submitted 2/13/2012, Accepted 5/23/2012. Authors Denev andKratchanova are with Laboratory of Biologically Active Substances, 139 Ruski Blvd, Plovdiv-4000, Bulgaria, Author Kratchanov is with Vitanea Ltd., 20 d-r G.M.Dimitrov str., Plovdiv-4000, Bulgaria, andAuthors Ciz andLojek are with Inst. of Biophysics of the Academy of Sciences of the Czech Republic,v.v.i.,Kralovopolska 135,612 65 Brno, by other enzymes like xanthine oxidase and xanthine dehydrogenase which reduce O 2 to O 2 ·− and by the auto-oxidation of many biomolecules like glyceraldehydes, FMNH 2 , FADH 2 , adrenalin, noradrenalin, and dopamine (Kirsch 2003). The most important source of O 2 ·− in vivo is the mitochondrial electron transport chain and hemoglobin in human erythrocytes, which also could be a source of superoxide radicals (Rifkind 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, oxygen and peroxynitrite can oxidize BH4 to quinonoid dihydrobiopterin, which readily rearranges to BH2 (50,51), and in vivo it has been shown that BH2 rapidly forms in the circulation following administration of BH4 (15). The authors consider changes to intracellular homeostasis as the most probable explanation for the increased oxidation of tetrahydrobiopterin as queuine deficiency has previously been suggested to affect the activity of a number of antioxidant systems (52,53) and to influence the metabolic state of the cell (33,52,54).…”
Section: Discussionmentioning
confidence: 99%